LTCC (Low Temperature Co-Fired Ceramic) inner electrode silver paste and preparation method thereof

By using a specific proportion of silver powder, organic carrier and sintering additives in LTCC technology, the warping and cracking problems of the device during co-firing are solved, and the good combination and smoothness of the silver layer and the ceramic substrate are achieved. Sintered, comply with environmental protection standards.

CN119207861AInactive Publication Date: 2024-12-27SUZHOU BETELY POLYMER MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411566936.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the co-firing process, the existing LTCC technology is prone to warping, bending and internal cracking and delamination of the device due to the different sintering characteristics of silver paste and ceramic membrane tape, which makes the device unable to be used normally.

Method used

The LTCC inner electrode silver paste was used in which 75% to 85% silver powder, 12% to 25% organic carrier, 0.5% to 4.0% sintering aid containing titanium, aluminum, and silicon, and 0.1% to 3.0% glass powder. The conductive silver paste is prepared through a specific mixing and grinding process to ensure good matching with the LTCC ceramic substrate and the flatness and density of the silver layer after sintering.

Benefits of technology

The good matching between the LTCC ceramic substrate and the conductive silver paste is achieved. After sintering, the silver layer is flat and dense, and the interface bonding force between the silver layer and the ceramic is strong, which avoids cracking of the inner layer and meets the lead-free and cadmium-free requirements of RoHS.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119492210000051
    Figure BDA0005119492210000051
Patent Text Reader

Abstract

The invention relates to an LTCC (Low Temperature Co-Fired Ceramic) inner electrode silver paste and a preparation method thereof, the LTCC inner electrode silver paste is used as a conductive silver paste for an LTCC ceramic substrate, and the LTCC inner electrode silver paste comprises the following components in percentage by mass: 75-85% of silver powder, 12-25% of an organic carrier, 0.5-4.0% of glass powder, 0.1-3.0% of a sintering aid and the balance of a solvent, the sintering aid is an organic aid containing titanium, aluminum and silicon elements; the silver powder comprises micro silver powder and superfine spherical silver powder, the mass of the superfine spherical silver powder is 5-20% of the total mass of the silver powder, the average particle size of the micro silver powder is 1.5-5 microns, and the average particle size of the superfine spherical silver powder is 0.3-1.0 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a surface material and a preparation technology thereof, and specifically to a LTCC inner electrode silver paste and a preparation method thereof. Background Art

[0002] Low Temperature Co-fired Ceramics (LTCC) technology is a multilayer ceramic manufacturing technology that integrates 3D high-density interconnection, passive components and IC packaging. It can realize the integration, miniaturization and multi-functionality of electronic components. Due to its good thermodynamics, electronics and corresponding mechanical properties, it is widely used in wireless communications, aerospace, military electronics and other fields.

[0003] The current LTCC green ceramic tape is doped with some low melting point oxides or low melting point glass to achieve low temperature sintering, which makes the existing traditional silver paste prone to matching failure. Due to the different sintering characteristics of the green ceramic tape and the silver paste, the device is very likely to warp and bend during the co-firing process, and in severe cases, internal cracking and delamination will occur, making the device unable to be used normally.

[0004] Therefore, it is necessary to provide a LTCC inner electrode silver paste and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a LTCC inner electrode silver paste and a preparation method thereof.

[0006] The present invention achieves the above object through the following technical solutions:

[0007] One of the technical solutions:

[0008] A LTCC inner electrode silver paste is used as a conductive silver paste for an LTCC ceramic substrate, and comprises the following components, calculated by mass percentage: 75% to 85% of silver powder, 12% to 25% of an organic carrier, 0.5% to 4.0% of glass powder, 0.1% to 3.0% of a sintering aid, and the remaining percentage of a solvent;

[0009] Sintering aids are organic additives containing titanium, aluminum, and silicon elements;

[0010] The silver powder includes micro silver powder and ultrafine spherical silver powder, wherein the mass of the ultrafine spherical silver powder is 5% to 20% of the total mass of the silver powder, the average particle size of the micro silver powder is 1.5 μm to 5 μm, and the average particle size of the ultrafine spherical silver powder is 0.3 μm to 1.0 μm.

[0011] Furthermore, the organic carrier includes a mixture of one or more of ethyl cellulose, acrylic resin, and cellulose acetate butyrate, and the organic carrier also includes a plasticizer and a solvent.

[0012] Furthermore, by weight percentage: 18% to 25% of one or more of ethyl cellulose, acrylic resin, and cellulose acetate butyrate, 3% to 8% of plasticizer, and 57% to 78% of solvent.

[0013] Furthermore, the plasticizer is a mixture of one or more of dibutyl phthalate, dioctyl phthalate, and tributyl citrate.

[0014] Furthermore, the solvent is a mixture of one or more of terpineol, butyl carbitol, butyl carbitol acetate, ethylene glycol ethyl ether acetate, ethylene glycol monobutyl ether, and cyclohexanone.

[0015] Furthermore, the auxiliary agent is a mixture of one or more of castor oil, fish oil, lecithin, tributyl phosphate, Span 85 and polymethacrylamide.

[0016] Furthermore, the sintering aid is a mixture of one or more titanium-containing, aluminum-containing, and silicon-containing functional sintering aids.

[0017] Furthermore, the melting temperature of the bismuth-containing glass powder is 500-830°C.

[0018] A method for preparing silver paste for LTCC inner electrodes, comprising the following steps:

[0019] 1) Mixing a polymer resin, a solvent and an additive in a certain proportion and fully dissolving them to obtain an organic carrier;

[0020] 2) mixing the organic carrier, silver powder and glass powder uniformly to obtain a premix;

[0021] 3) fully grinding the premix to obtain silver electrode slurry; filtering, testing and supplementing the silver electrode slurry with solvent to obtain the conductive silver slurry.

[0022] Compared with the prior art, the conductive silver paste prepared by the present invention has good matching with the LTCC ceramic substrate after co-firing. After the conductive silver paste is sintered, the silver layer is flat and dense, the silver layer has strong bonding force with the ceramic interface, the device is flat, and there is no cracking and delamination inside; and it does not contain lead and cadmium, meeting the requirements of RoHS. DETAILED DESCRIPTION

[0023] Embodiment 1:

[0024] This embodiment shows a method for preparing a LTCC conductive silver paste, the process comprising:

[0025] Preparation of organic carrier: 15% of ethyl cellulose, 5% of acrylic resin, 3% of dibutyl phthalate, and 77% of butyl carbitol were added into a reaction kettle by weight percentage, and stirred at 70° C. for 2 hours to obtain an organic carrier.

[0026] Low-temperature sintering LTCC conductive silver paste: 80% of silver powder, 2.0% of bismuth-containing glass powder, 15.5% of the above-mentioned organic carrier, 0.5% of tributyl phosphate, and 2.0% of titanium-containing additive are mixed and pre-stirred by weight, and then placed in a disperser at a speed of 300rpm / min for 4 hours. The stirred slurry is mixed and ground 8 times by a three-roll grinder until the fineness is less than or equal to 10μm, and filtered to obtain low-temperature sintering LTCC conductive silver paste. Among them, the weight ratio of micro silver powder and ultrafine spherical silver powder in the silver powder is that the mass of ultrafine spherical silver powder accounts for 8% of the total mass of silver powder, and the remaining mass of silver powder is the mass of micro silver powder.

[0027] Embodiment 2:

[0028] This embodiment shows a method for preparing a LTCC conductive silver paste, the process comprising:

[0029] Preparation of organic carrier: 13.5% of ethyl cellulose, 7.5% of acrylic resin, 3.5% of dibutyl phthalate, and 75.5% of butyl carbitol acetate were added into a reaction kettle by weight percentage, and stirred at 70° C. for 2 hours to obtain an organic carrier.

[0030] Low-temperature sintering LTCC conductive silver paste: 83% of silver powder, 1.5% of bismuth-containing glass powder, 13.5% of the above-mentioned organic carrier, 0.5% of castor oil, and 1.5% of aluminum-containing additive are mixed and pre-stirred by weight, and then placed in a disperser at a speed of 300rpm / min for 4 hours. The stirred slurry is mixed and ground 8 times by a three-roll grinder until the fineness is less than or equal to 10μm, and filtered to obtain low-temperature sintering LTCC conductive silver paste. Among them, the weight ratio of micro silver powder and ultrafine spherical silver powder in the silver powder is that the mass of ultrafine spherical silver powder accounts for 14% of the total mass of silver powder, and the remaining mass of silver powder is the mass of micro silver powder.

[0031] Embodiment 3:

[0032] This embodiment shows a method for preparing a LTCC conductive silver paste, the process comprising:

[0033] Preparation of organic carrier: 15.5% of ethyl cellulose, 5.5% of acrylic resin, 4.5% of tributyl citrate, and 74.5% of butyl carbitol were added into a reaction kettle by weight, and stirred at 70° C. for 3 hours to obtain an organic carrier.

[0034] Low-temperature sintered LTCC conductive silver paste: 81.7% silver powder, 1.8% bismuth-containing glass powder, 15.0% of the above-mentioned organic carrier, 0.5% Siban 85, and 1.0% silicon-containing additive were mixed and pre-stirred by weight percentage, and then placed in a disperser at a speed of 300rpm / min for 4 hours. The stirred slurry was mixed and ground 8 times by a three-roll grinder until the fineness was less than or equal to 10μm, and filtered to obtain low-temperature sintered LTCC conductive silver paste. Among them, the weight ratio of micro silver powder and ultrafine spherical silver powder in the silver powder is that the mass of ultrafine spherical silver powder accounts for 10% of the total mass of silver powder, and the remaining mass of silver powder is the mass of micro silver powder.

[0035] Embodiment 4:

[0036] This embodiment shows a method for preparing a LTCC conductive silver paste, the process comprising:

[0037] Preparation of organic carrier: 14.5% of ethyl cellulose, 6.5% of acrylic resin, 5.5% of dioctyl phthalate, and 73.5% of butyl carbitol were added into a reaction kettle by weight, and stirred at 70° C. for 3 hours to obtain an organic carrier.

[0038] Low-temperature sintering LTCC conductive silver paste: 80.0% silver powder, 1.5% bismuth-containing glass powder, 16.0% of the above organic carrier, 0.5% castor oil, 0.5% titanium-containing additive and 1.5% aluminum-containing additive are mixed and pre-stirred by weight, and then placed in a disperser at a speed of 350rpm / min for 4 hours. The stirred slurry is mixed and ground 8 times by a three-roll grinder until the fineness is less than or equal to 10μm, and filtered to obtain low-temperature sintering LTCC conductive silver paste. Among them, the weight ratio of micro silver powder to ultrafine spherical silver powder in the silver powder is that the mass of ultrafine spherical silver powder accounts for 12% of the total mass of silver powder, and the remaining mass of silver powder is the mass of micro silver powder.

[0039] Embodiment 5:

[0040] This embodiment shows a method for preparing a LTCC conductive silver paste, the process comprising:

[0041] Preparation of organic carrier: 16.5% of ethyl cellulose, 5.5% of acrylic resin, 3.5% of tributyl citrate, and 74.5% of butyl carbitol were added into a reaction kettle by weight, and stirred at 70° C. for 2.5 hours to obtain an organic carrier.

[0042] Low-temperature sintering LTCC conductive silver paste: According to weight percentage, 78.0% silver powder, 1.8% bismuth-containing glass powder, 17.4% of the above organic carrier, 0.5% tributyl phosphate, 0.8% silicon-containing additive and 1.5% aluminum-containing additive are mixed and pre-stirred, and then placed in a disperser at a speed of 300rpm / min for 4 hours. The stirred slurry is mixed and ground 8 times in a three-roll grinder until the fineness is less than or equal to 10μm, and filtered to obtain low-temperature sintering LTCC conductive silver paste. Among them, the weight ratio of micro silver powder and ultrafine spherical silver powder in the silver powder is that the mass of ultrafine spherical silver powder accounts for 14% of the total mass of silver powder, and the remaining mass of silver powder is the mass of micro silver powder.

[0043] Comparative Example 1:

[0044] This comparative example provides a method for preparing a conductive silver paste, the process comprising:

[0045] Preparation of organic carrier: 15.5% of ethyl cellulose, 5.5% of acrylic resin, 4.5% of dibutyl phthalate, and 74.5% of butyl carbitol were added into a reaction kettle by weight, and stirred at 70° C. for 2 hours to obtain an organic carrier.

[0046] Low-temperature sintered LTCC conductive silver paste: 82% of silver powder, 2.5% of bismuth-containing glass powder, 15.0% of the above-mentioned organic vehicle, and 0.5% of tributyl phosphate are mixed and pre-stirred by weight, and then placed in a disperser and stirred at a speed of 300 rpm / min for 4 hours. The stirred slurry is mixed and ground 8 times by a three-roll grinder until the fineness is less than or equal to 10 μm, and filtered to obtain low-temperature sintered LTCC conductive silver paste. Among them, the weight ratio of micro silver powder and ultrafine spherical silver powder in the silver powder is that the mass of ultrafine spherical silver powder accounts for 10% of the total mass of the silver powder, and the remaining mass of the silver powder is the mass of micro silver powder.

[0047] Comparative Example 2:

[0048] This comparative example provides a method for preparing a conductive silver paste, the process comprising:

[0049] Preparation of organic carrier: 15.5% of ethyl cellulose, 5.5% of acrylic resin, 4.5% of dibutyl phthalate, and 74.5% of butyl carbitol were added into a reaction kettle by weight, and stirred at 70° C. for 2 hours to obtain an organic carrier.

[0050] Low-temperature sintering LTCC conductive silver paste: 82% silver powder, 2.5% bismuth-containing glass powder, 15.0% of the above-mentioned organic carrier, 0.5% castor oil, and 2.0% polyester additives are mixed and pre-stirred by weight, and then placed in a disperser at a speed of 300rpm / min for 4 hours. The stirred slurry is mixed and ground 8 times by a three-roll grinder until the fineness is less than or equal to 10μm, and filtered to obtain low-temperature sintering LTCC conductive silver paste. Among them, the weight ratio of micro silver powder and ultrafine spherical silver powder in the silver powder is that the mass of ultrafine spherical silver powder accounts for 10% of the total mass of silver powder, and the remaining mass of silver powder is the mass of micro silver powder.

[0051] Test example:

[0052] The conductive silver pastes in Examples 1-3 and Comparative Examples 1-2 were respectively printed on a ceramic substrate using a 250-mesh stainless steel screen, and then sintered. The sintering conditions included: sintering in a tunnel furnace atmosphere, a peak temperature of 850±5°C, and a peak time of 10 minutes. Afterwards, each sample was tested for device warpage, delamination cracking, adhesion, and conductivity. The test results are shown in Table 1.

[0053] Table 1:

[0054]

[0055] Through the test examples, it can be obtained that: it has good co-firing matching with the LTCC ceramic substrate, the flatness of the device after sintering is good, the silver layer and the ceramic interface have strong bonding, there is no delamination and cracking, and the silver layer after sintering is flat and dense, maintaining good conductivity. With the promotion of LTCC technology, the conductive silver paste of the present invention and its preparation method have huge market value.

[0056] Compared with the prior art, the conductive silver paste prepared by the present invention has good matching with the LTCC ceramic substrate after co-firing. After the conductive silver paste is sintered, the silver layer is flat and dense, the silver layer has strong bonding force with the ceramic interface, the device is flat, and there is no cracking and delamination inside; and it does not contain lead and cadmium, meeting the requirements of RoHS.

[0057] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A LTCC internal electrode silver paste, characterized in that: Used as a conductive silver paste for LTCC ceramic substrates, calculated by mass percentage, including the following components: 75% to 85% silver powder, 12% to 25% organic carrier, 0.5% to 4.0% glass powder and 0.1% to 3.0% sintering aid, and the remaining percentage is solvent; Sintering aids are organic additives containing titanium, aluminum, and silicon elements; The silver powder includes micro silver powder and ultrafine spherical silver powder, wherein the mass of the ultrafine spherical silver powder is 5% to 20% of the total mass of the silver powder, the average particle size of the micro silver powder is 1.5 μm to 5 μm, and the average particle size of the ultrafine spherical silver powder is 0.3 μm to 1.0 μm.

2. The LTCC inner electrode silver paste according to claim 1, characterized in that: The organic carrier includes a mixture of one or more of ethyl cellulose, acrylic resin, and cellulose acetate butyrate. The organic carrier also includes a plasticizer and a solvent.

3. The LTCC inner electrode silver paste according to claim 2, characterized in that: Calculated by weight percentage: 18% to 25% of one or more of ethyl cellulose, acrylic resin, and cellulose acetate butyrate, 3% to 8% of plasticizer, and 57% to 78% of solvent.

4. The LTCC inner electrode silver paste according to claim 3, characterized in that: The plasticizer is a mixture of one or more of dibutyl phthalate, dioctyl phthalate and tributyl citrate.

5. The LTCC inner electrode silver paste according to claim 4, characterized in that: The solvent is a mixture of one or more of pineneol, butyl carbitol, butyl carbitol acetate, ethylene glycol ethyl ether acetate, ethylene glycol monobutyl ether and cyclohexanone.

6. The LTCC inner electrode silver paste according to claim 5, characterized in that: The auxiliary agent is a mixture of one or more of castor oil, fish oil, lecithin, tributyl phosphate, Span 85 and polymethacrylic acid amine.

7. The LTCC inner electrode silver paste according to claim 6, characterized in that: The sintering aid is a mixture of one or more functional sintering aids containing titanium, aluminum and silicon.

8. The LTCC inner electrode silver paste according to claim 7, characterized in that: The melting temperature of the bismuth-containing glass powder is 500-830°C.

9. A method for preparing a silver paste for an inner electrode of LTCC, used for preparing the silver paste for an inner electrode of LTCC according to any one of claims 1 to 8, characterized in that: The steps are: 1) Mixing a polymer resin, a solvent and an additive in a certain proportion and fully dissolving them to obtain an organic carrier; 2) mixing the organic carrier, silver powder and glass powder uniformly to obtain a premix; 3) fully grinding the premix to obtain silver electrode slurry; filtering, testing and supplementing the silver electrode slurry with solvent to obtain the conductive silver slurry.

Citation Information

Patent Citations

  • Conductive silver paste for ceramic filter and preparation method thereof

    CN111489848A

  • External electrode silver paste for low-temperature sintering LTCC (Low Temperature Co-Fired Ceramic) device and preparation method thereof

    CN117524541A

  • P-region conductive paste for xBC battery, preparation method, electrode and battery

    CN118197676A